Evaluation of cutting ability and plastic deformation of reciprocating files - Alexandre KOWALCZUCK; Gilson Blitzkow SYDNEY; Elizabeth Ferreira MARTINEZ; Rielson José Alves CARDOSO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This in vitro study evaluated the cutting ability of reciprocating files and the deformations caused by their multiple use. Five Reciproc® R25 files were divided into five groups for 10 simulated root canal preparations each. The resin blocks were weighed and photographed (12.5X and 20X) before and after preparation. The canals were prepared according to the manufacturer's instructions. Enlargement of the root canals was evaluated by comparison of pre- and post-preparation images using a computer software. The preoperative and postoperative weight differences determined the cutting ability of repeatedly used instruments. The data were analyzed using Lilliefors and Friedman statistical tests. The cutting ability and enlargement of the canals gradually decreased after each use, with significant differences observed at the 8th and 9th repetitions, respectively. There was no evidence of file deformation. The cutting ability and enlargement of the simulated canals gradually decreased when a reciprocating file was used up to 10 times.